Effect of yeast culture (YEA-SACC1026) supplement on fermentation and in sacco digestibility of some roughages in buffalo calves - SINGLA, MONIKA; KUMAR, UMESH; SAREEN, VIJAY KUMAR; SINGH, SUDARSHAN (The Indian Journal of Animal Sciences, 2013)
The effect of Saccharomyces cereviswe culture (YC, YEA-SACC1026) as a supplement to nDrmal diet of buffalo calves on the rumen microbial population and fermentation pattern and in sacco dry matter and cell wall constituents disappearance of some feedstuffs was monitored on 6 rumen-fistulated buffalo calves divided into 2 groups C and yc. All the animals were fed on a conventional diet comprising wheat straw, berseem and concentrate mixture as per requirements. The animals of group YC Were supplemented with 5 g yeast culture per day. The pH Was incrensed significantly and lactate concentration deercased in rumen fluid (RF) for up to 6 hr post-feeding in YC compared to C group. Total bacteria, toral viable bacteria and cellulolytic bactcria population increased significantly in YC group.The cuncentation of total VFA and protein was increased by 8.36 and 2.50%, respectively, in YC compared to C group. On YC supplementation, the concentration of NH3-N in RF decreased by 9.26%. The in sacco dry matter, neutral detergent fibre and cellulose disappearance of wheat straw, rice straw, pearl millet straw, maize stalks and bel seem hay was higher in yeast supplemented group compared to control.